Formulation of Breakfast Porridges from Three Nigerian Legumes-Afzelia africana (Counterwood Seed), Detarium microcarpium (Tallow Seed) and Sphenostylis stenocarpa (African Yambean Seed) Blended with Corn Flour: Their Nutrient Composi - Onyechi, Uchenna Agatha; Ibeanu, Vivinnene Nkiruka; Gift, Nkechiyere (Pakistan Journal of Nutrition, 2014)
In this study breakfast porridges were formulated based on three indigenous Nigerian legumes-Afzelia africana-AA, (Counterwood seed), Detarium microcarpium-DT (Tallow seed) and Sphenostylis stenocarpa-SS, (African Yam bean). The food items were processed into flour using the traditional methods. The flours were blended with corn and made into porridges: CAA (corn and Afzelia africana), CDM (corn and Detarium microcarpium) and CSS (corn and Sphenostylis stenocarpa) flours. The nutrients composition of the porridges was determined using standard methods and sensory evaluation was conducted using nine point Hedonic scale. Data was analyzed using descriptive statistics and ANOVA. The result revealed that the crude protein content of CSS (3.30%) was significantly higher (p